Common controls driven conceptual leadership framework - Petteri Mussalo; Virpi Hotti; Anastasia Kirjanen; Henna Lauronen; Jukka Holopainen; Hannu Härkönen; Juho Huikari (Finnish Social and Health Informatics Association, 2018)
The forthcoming social welfare and healthcare reform in Finland with its organizational, financing and steering changes challenges the leadership. All service systems levels of the social welfare and healthcare have to achieve performance objectives whilst at the same time also meeting conformance requirements. However, there are hundreds authority documents (e.g., best practices, guidelines, regulations and standards) the common controls of which are adapted partly manually and partly by leveraging automation in organizations. Leaders review and develop their practices around performance and conformity (i.e., conformance or compliance) within frameworks that are mainly the sets of principles. However, the common controls affect into the main tasks of the governance (i.e., direct, evaluate and monitor). Therefore, we construct a conceptual leadership framework to highlight the meaning of the common controls and the meaning of criteria for performance and conformity. The constructed framework contains the terms (e.g., a control objective, decision criteria, event, insight, and transaction) that are mainly defined in the glossaries of the authority documents. The terms are used to find out terms and definitions for the leadership framework to figure out cognitive meanings for the concepts of the common controls driven leadership.